Pengaruh Ekstrakurikuler Seni Baleganjur Terhadap Kepercayaan Diri Siswa Di SD Negeri 20 Cakranegara - Karyasa, Teguh; Rasmini, Ni Wayan; Prajawati, Yani Timor (Institut Agama Hindu Negeri Gde Pudja Mataram, 2025)
This research was conducted with the aim of analyzing the influence of each Baleganjur Arts Extracurricular variable on Student Self-Confidence at SD Negeri 20 Cakranegara. The research approach used is associative quantitative with data collection techniques, namely observation, questionnaires and documentation, while the data analysis used is simple linear regression analysis. The population in this research is all students who take part in the Baleganjur arts extracurricular at SD Negeri 20 Cakranegara. The sample size was determined using purposive sampling. The population obtained by calculation was 40 sample students. This research uses Simple Linear Regression analysis tools through validity tests, reliability tests and normality tests. The results of the research show that there is a positive influence from implementing the Baleganjur arts extracurricular on students' self-confidence at SD Negeri 20 Cakranegara.